Dentist's Appearance: Does It Matter? - Ahmad Dhamiri Ramainor; Intan Munirah Azizol; Nurjehan Binti Mohamed Ibrahim; Aspalilah Alias (USIM Press, Universiti Sains Islam Malaysia, 2024)
Volume: 7 Issue: 2(page: 70–75)